Basic Income and the Gendered Division of Labour - Elgarte, Julieta Magdalena (2008)
A basic income has been regarded as a policy that could advance gender justice because of its ability to protect women from some of the consequences of the gendered division of labour. I argue, though, that full justice for women plausibly entails the abolishment of traditional gender roles and that a feminist assessment of basic income should then look at its ability to help us move away from traditional gender roles. I also argue that basic income could meet the demands we should place on our income security policy as we move towards a gender-just society; and I defend basic income against the objection that, given current gender norms, it might lead to a reinforcement of the gendered division of labour.